Analisis Kinerja Dana Bergulir PNPM Mandiri di Kecamatan Lubuk Begalung Kota Padang - Surya, Sari (Business Administration Study Program - Universitas Katolik Parahyangan, 2011)
This study is aimed at evaluating financial performance of micro and small en-terprises and social economic impact of governmentâs community-based povertyalleviation program (PNPM Mandiri). Evaluation focuses on comparing the financialratios and social economic indicators before and after using of the revolving fund.Improvement on these ratios and indicators is argued as one of indications for povertyalleviation. Data were collected from owner of 80 micro and small enterprises in8 Kelurahan. Based on Wilcoxon singed-rank test, the results are varies. There isno significant difference in current ratio, quick ratio and return on equity of thesemicro and small enterprises before and after using the revolving fund, while there issignificant difference in cash ratio, return on asset and net profit margin. Meanwhilefive out of six social economic indicators are significantly different.Keywords: Financial performance, financial ratio, social economic impact, povertyalleviation, PNPM Mandiri1